Privatization of maritime security surveillance and enforcement: a compromise of state sovereignty - Syed Abdul Kader , Sharifah Zubaidah; Abdulrazaq, Abdulkadir. O. (The International Institute for Science, Technology and Education (IISTE), 2013)
One of the most vital engines motivating global economic progress and development in recent times is the freedom to participate in seaborne trade the world over. Moderately unhindered right to traverse the world's ports is an essential component of the global economic success and development story. In the like manner, the serious threats posed to global order by international terrorism, piracy, oil theft and bunkering, to mention but a few, have given rise to overriding and all important national security concerns among the port states. In response to these challenges, some states have increased their strategy with the establishment of maritime security enforcement forces like the Coast Guard in U.S, the Malaysian Maritime Enforcement Agency (MMEA) in Malaysia and the Nigerian Maritime Administration and Safety Agency (NIMASA), to address the problem. However, the Nigerian government has now changed the policy and firmed-out enforcement and surveillance activities in the entire Nigerian maritime domain to a private security company. This paper argues that the issue of maritime enforcement and surveillance goes beyond the activities of private individuals and besides, the policy usurps the constitutional powers of the legislature which established NIMASA through an Act of the National assembly as well as the responsibility of the navy. The paper also maintains that the concession of maritime surveillance and enforcement to a private security company is a total misunderstanding of the use of private security companies in maritime practice and by so doing it amounts to a compromise of national sovereign in the hands of a few private individuals.